Decellularized liver bioscaffold: a histological and immunohistochemical comparison between normal, fibrotic and hepatocellular carcinoma - Salim, Mohamed S. (Clin Exp Hepatol, 2019)
AIM OF THE STUDY: Increasing demand for liver transplantation represents an important health burden. Decellularized liver bioscaffold can be a suitable alternative for whole organ transplantation. However, various pathologies can affect the structure of decellularized scaffolds. This work discusses differences between hepatic fibrosis (HF), hepatocellular carcinoma (HCC) and normal decellularized liver bioscaffolds. MATERIAL AND METHODS: Murine models of HF and HCC were created, livers from normal, HF and HCC were decellularized, and evaluation of decellularization was done using morphological, histological and DNA analysis examination. Also, immunohistochemical staining using collagen, laminin, fibronectin and alphafetoprotein was done. Deposition area and intensity of the used immunohistochemical staining in liver capsules and the staining deposition thickness in the blood vessels and hepatic capsule walls were measured for comparison between the three models. RESULTS: Normal, HF and HCC livers were decellularized efficiently as confirmed by histological and DNA estimation. HCC decellularized samples showed significantly higher collagen, fibronectin and laminin deposition in both capsule and blood vessels, followed by HF decellularized samples, which also showed the highest thickness of laminin deposition in both capsule and blood vessels, then the normal model, which recorded the lowest value. Alphafetoprotein positive cells were absent in normal and HF, with rare cells in HCC. CONCLUSIONS: Even pathologic livers, HF and HCC, can be efficiently decellularized, showing normal morphology and architecture. However, HCC and HF showed significantly higher deposition of extracellular matrix proteins: collagen, fibronectin and laminin. The impact of these differences on physiological and immunological functions of the bioscaffold requires recellularization experiments.